Nonaccidental Trauma Is an Independent Risk Factor for Mortality Among Injured Infants. Issue 12 (December 2021) - Delaplain, Patrick T.; Grigorian, Areg; Won, Eugene; Dosch, Austin R.; Schubl, Sebastian; Covarrubias, Jose; Nahmias, Jeffry
Abstract : Objectives: The Centers for Disease Control disclosed over 600, 000 cases of child abuse or neglect in 2016. Single-institution studies have shown that nonaccidental trauma (NAT) has higher complication rates than accidental trauma (AT). Nonaccidental trauma is disproportionately represented in infants. We hypothesized that NAT would increase the risk of mortality in infants. This study aims to provide a contemporary descriptive analysis for infant trauma patients and determine the association between NAT and mortality. Methods: Infants (<1 year of age) within the Pediatric Trauma Quality Improvement Program database (2014–2016) were identified. Descriptive statistics (χ 2 and t test) were used to compare NAT infants to AT infants. A multivariable logistic regression was used to determine the risk of mortality associated with select variables including NAT. Results: From 14, 965 infant traumas, most presented to a level I pediatric trauma center (53.5%) with a median injury severity score of 9. The most common mechanism was falls (48.6%), followed by NAT (14.5%). Overall mortality was 2.1%. Although most NAT infants were white (60.2%), black infants were overrepresented (23.6% vs 18.3%; P < 0.0001) compared with AT infants. The incidence of mortality was higher in NAT infants (41.6% vs 13.9%; P < 0.0001), and they were more likely to have traumatic brain injury (TBI) (63.1% vs 50.6%; P < 0.001). Nonaccidental trauma [odds ratio (OR), 2.48; P < 0.001], hypotension within 24 hours (OR, 8.93; P < 0.001), injury severity score (OR, 1.12; P < 0.001), and severe abbreviated injury scale-head (OR 1.62, P = 0.014) had the highest association with mortality. Conclusions: This study confirms the incidence of TBI and NAT in infants. Although providers should be vigilant for NAT, suspicion of NAT should prompt close surveillance, as there is a 2-fold increased risk of mortality independent of injury or TBI.